PENGARUH LEVERAGE, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS (STUDI KASUS PADA PERUSAHAAN SUB SECTOR REAL ESTATE AND PROPERTY DI BURSA EFEK INDONESIA PERIODE 2015-2018) - Pingkan Saraswati (JURNAL ILMIAH EDUNOMIKA, 2020)
Profitabilitya has significance for theecompany because it is one of the bases for evaluating the condition of a company. The level off profitability describes the ecompany's performance as seen from the company's ability to generate profits. Profitability in this study is calculated by return on assets (ROA) because it can show how the company's performance is nseenn from the overall use of assets owned by the company in generating profits. Thissstudyyaims to examine the leverage, liquidity, and size off thee company yaffect the eprofitability. The ssampling ttechniqueu used in this study wass purposivee samplingg, which issaa sample technique ethat uses certain ncriteria.. There earee16 companies ethat are sampled in this sstudy.mThe nanalysiss techniquee usedd is multiplee linearr regressionn using SPSS version 22. Multiplee linear regression analysis susess the eclassicc assumption ntest, nincluding mthe nnormality ntest, multicollonityy test,,heteroscedasticityytest,, and dautocorrelationn test.m Tootestttheevariablessused theecoefficient of determination test, t-test, f-test. The results of this study indicate that there is no significant effect on the variable leverage on profitability. Liquidity hass a positivee effectt onn profitability. There eis snoo significantt effectt off thee Company Size variablee on nthee profitability variable..